Barriers and enablers for school leaders implementing PB4L Tier 2 with fidelity in New Zealand secondary schools : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education, Educational Administration and Leadership Subject at Massey University, Manawatū, New Zealand - Andrews, Stephanie Tania (Massey University, 2019)
This thesis explores the barriers and enablers to implementing Positive Behaviour for Learning (PB4L) Tier 2 with fidelity in New Zealand secondary schools. PB4L was introduced to New Zealand schools in 2010. It provides a framework that schools use to guide the implementation of evidence-based practice with the goal of reducing problem behaviour and providing a positive school culture. With a focus on evidence-based practice, fidelity of implementation is a core principle of PB4L. PB4L consists of three tiers that provide a continuum of behaviour supports for students. Tier 2 of the continuum targets approximately 15% of students within a school and offers small group response before students develop habitual patterns of behaviour. This mixed method, sequential explanatory design was conducted in two phases. In Phase I a quantitative survey was administered to principals and Tier 2 team leaders in New Zealand secondary schools. This was used to identify the extent to which schools were implementing Tier 2 interventions within their school, and to the identify barriers and enablers schools were experiencing in implementing PB4L Tier 2. In Phase II qualitative data was collected through semi-structured interviews with PB4L Tier 2 team leaders who had a wide range of experiences in the implementation of PB4L Tier 2, adding depth of explanation to the quantitative data. A number of barriers and enablers were identified, often the barrier or enabler was a different side of the same coin. Key enablers that emerged from this mixed methods research included the facilitation of shared learning between secondary schools, schools establishing strong external relationships with outside agencies, and proactive school leadership. Significant barriers included the time investment required to achieve ‘fidelity’ in interventions, efficient access to data, the complexity of the secondary environment and the limited range of easily resourced evidence-based interventions for use in a secondary school context.
Keywords: School discipline; New Zealand; Problem children; Behavior modification; High schools; High school teachers; Attitudes; 390403 Educational administration, management and leadership